2013
DOI: 10.1016/j.jcrysgro.2012.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Laser-diode-heated floating zone (LDFZ) method appropriate to crystal growth of incongruently melting materials

Abstract: We have developed the laser-diode-heated floating zone (LDFZ) method, in order to improve the broad and inhomogeneous light focusing in the conventional lamp-heated floating zone method, which often causes difficulties in the crystal growth especially for the incongruently melting materials. We have simulated the light focusing properties of the LDFZ method to make irradiated light homogeneous and restricted mostly to the molten zone. We have designed and assembled an LDFZ furnace, and have demonstrated how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…Single crystals of BaSrCo 2 Fe 11 AlO 22 of nominal composition were grown by the traveling solvent floating zone method under 10 atm of pure oxygen with use of the laser floating zone furnace (SC1-LD200x5, Canon Machinery Inc.). The floating zone furnace used in this study was similar to that reported by Ito et al 27 , but equipped with five laser diodes. The maximum power of each laser diode was 200 W. Sintered polycrystalline rods of nominal composition were used as both feed and seed rods in the first growth, while the grown single crystal was used as a seed rod for the next growth.…”
Section: Methodsmentioning
confidence: 90%
“…Single crystals of BaSrCo 2 Fe 11 AlO 22 of nominal composition were grown by the traveling solvent floating zone method under 10 atm of pure oxygen with use of the laser floating zone furnace (SC1-LD200x5, Canon Machinery Inc.). The floating zone furnace used in this study was similar to that reported by Ito et al 27 , but equipped with five laser diodes. The maximum power of each laser diode was 200 W. Sintered polycrystalline rods of nominal composition were used as both feed and seed rods in the first growth, while the grown single crystal was used as a seed rod for the next growth.…”
Section: Methodsmentioning
confidence: 90%
“…Single crystals of La 2−x Ba x CuO 4 (near x = 1/8) were grown using the recently developed laser-diode-heated floating zone method, which enables an exceptionally high degree of sample homogeneity [24]. The samples were cut along the crystal axes into rectangular bars for a − b plane transport measurements.…”
Section: B Methods and Resultsmentioning
confidence: 99%
“…Multiple Broken Symmetries in Striped La 2−x Ba x CuO 4 detected by the Field Symmetric Nernst Effect S I. SAMPLE PREPARATION Single crystals of La 2−x Ba x CuO 4 (near x = 1/8) were grown using the recently developed laser-diode-heated floating zone method, which enables an exceptionally high degree of sample homogeneity, as shown by the absence of impurity phases in Laue and x-ray diffraction measurements [24]. The samples were cut along the crystal axes into rectangular bars for a − b plane transport measurements, with typical dimensions of 3.0 × 0.5 × 0.5 mm for in-plane resistivity (ρ xx ) measurements and 3.0 × 1.5 × 0.5 mm for thermoelectric and Hall measurements .…”
Section: Supplementary Materials Formentioning
confidence: 99%
“…However, the conventional FZ method is difficult to apply to refractory materials with a high melting temperature, volatile materials or incongruent materials. To partly overcome this difficulty, the FZ method using a diode laser, referred to as the LFZ method hereafter, has recently been proposed [5]. This LFZ instrument, composed of seven diode lasers with each power of 50W, has successfully shown many advantageous properties over the conventional halogen lamp or xenon lamp FZ method.…”
Section: Introductionmentioning
confidence: 99%